Есть, молиться, любить - Гилберт Элизабет (Роскет&travel, 2013)
Экземпляры: ф.24 (20190726) / Инвентарный номер: 57498 / Цена: 50.00 / Сис.шифр: 84(4Вел) / Авт.знак: Г 47 / ГРНТИ: 17.82.30 / ББК: 84(4Вел)